SOLID AND ALTERNATIVES FORMS FOR ORAL ADMINISTRATION IN PEDIATRICS - Joana Marto; Ana Salgado; António Almeida (Formifarma, LDA., 2011)
Despite the high number of medicines on the market, few are specifically indicated for the paediatric population. This problem has usually been solved through the prescription of dosage forms that are often inadequate or contain inadequate doses for paediatric patients. Consequently, the prescription of off-label medicines and the preparation of compounded drugs have taken a prominent role in paediatrics as a way to fill the existent gaps. Thus the development of appropriate medicines for children is of the utmost importance, so the choice of the dosage form is made according to the needs of the paediatric subpopulations to which they are intended, since their aim is not only the compliance but mainly the safety of prescribed medicine. Surveys carried out by the pharmaceutical industry show innovative dosage forms, such as orodispersible systems, oral lyophilisates, multi-particulate systems obtained by microencapsulation, minitablets, oromucosal preparations and their derivatives. Novel administration and primary container-closure systems in order to facilitate the paediatric administration have also been licensed. This article is a critical review of the most recent therapeutic systems for oral administration of medicines in children, as well as of the main innovative issues therein involved.